De jas van het onderzoek ofwel de weg naar het behoud van onze monumenten (Bulletin KNOB, 2003)
In the Netherlands a lot of matters are made subordinate to economic interests and the urge for economic progress is imperative. Culture must be economised. In addition, the large number of infrastructural measures, taken by the authorities in order to clear the way for passenger travel and goods transport, pose a threat to this part of our cultural heritage. This fate does not only affect the visible monuments.Things are even worse for non-visible monuments, such as castle grounds, frequently without protected status, as well as for the non-protected direct surroundings of a protected country estate or castle.The research of SKLN, NKS and the Stichting Limburgse Kastelen (Foundation for castles in the Province of Limburg) into the lost and still existing castles and country estates in this Province is intended to show why it is worthwhile to make an effort for their conservation.We want to be more explicit and active in our intentions. If we fail to do so, we may have to tell our children and grandchildren stories about castles and country estates as phenomena from bygone times, like fairy tales, and all that may be left of these splendid buildings will be romantic fantasies about them.